Peran Penyuluh dan Tingkat Pengetahuan Petani Terhadap Teknologi Budidaya Padi Berbasis Pertanian Cerdas Iklim di Desa Puyung Kecamatan Jonggat, Kabupaten Lombok Tengah - Dian Mirawati; Hayati Hayati; Muktasam Muktasam (Universitas Mataram, 2023)
The purpose of this research was to examine information about the role of extension workers, the level of farmers knowledge, and the relationship between the role of extension workers and the level of knowledge of farmers on climate smart agricultural technology in Puyung Village, Jonggat District, Central Lombok Regency, West Nusa Tenggara Province. The research design used, namely a quantitative approach. The number of respondents was 29 farmers. The data that has been collected is tabulated and analyzed descriptively using the Minitab 16 software and multiple linear regression. Based on the results of this research, the percentage of extension agents roles as dynamists and facilitators for climate-smart agriculture is 89.77% and 84.67%, the level of farmers knowledge of the technology is an average of 90.86%, and the relationship between the role of extension workers and the level of knowledge of farmers has a strong correlation and has an influence of 53.7%.